The “SUPER” Program to Increase Marital Satisfaction - Ika Rizki Ramadhani; Tina Afiatin (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2020)
A successful marriage can be achieved by aiming for a satisfying marriage. The low level of marital satisfaction causes various problems in marriage that might lead to divorce. The aim of this study was to determine the effect of the “SUPER” program in increasing marital satisfaction. The "SUPER" program is a gratitude intervention based on techniques of building sense of gratitude. Participants in this study were 12 married women with marriage period ranging from 1 to 10 years who were divided into two groups: 6 women in experimental group and 6 women in control group). The experiment in this study used untreated control group design with pretest-posttest and analyzed using Mann-Whitney U test. Data analysis results showed that there was significant difference in marital satisfaction scores between experimental and control group (Z= -2.098, p<0.05). The Wilcoxon Signed-rank test conducted on experimental group found that there was significant increase in marital satisfaction score from pretest to posttest (Z= -1.992, p<0.05). Therefore, it can be concluded that the “SUPER” program can increase marital satisfaction in married women. Marital satisfaction aspects that had increased were cognitive, interaction patterns, social support, and physiological aspects. Cognitive aspect had the highest score increase compared to other aspects.